2005
DOI: 10.1191/1352458505ms1185oa
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of valacyclovir in multiple sclerosis

Abstract: Although not statistically significant, positive trends were detected for acyclovir by clinical measures, but not by MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 24 publications
0
47
0
1
Order By: Relevance
“…Nevertheless, a significant reduction in the number of new, active, MRI-evident lesions in a subgroup of patients with high disease activity was seen [69]. An American two-year placebo-controlled, doubleblind, clinical trial with valaciclovir has recently been reported to provide positive trends by clinical measures, although these were not statistical significant [70].…”
Section: Controlled Trials Of Antiviral Chemotherapymentioning
confidence: 96%
“…Nevertheless, a significant reduction in the number of new, active, MRI-evident lesions in a subgroup of patients with high disease activity was seen [69]. An American two-year placebo-controlled, doubleblind, clinical trial with valaciclovir has recently been reported to provide positive trends by clinical measures, although these were not statistical significant [70].…”
Section: Controlled Trials Of Antiviral Chemotherapymentioning
confidence: 96%
“…Following oral administration, valacyclovir is rapidly and nearly completely hydrolyzed to acyclovir by first-pass intestinal and hepatic metabolism (13,27). Acyclovir crosses the blood-brain barrier, a desirable quality for the treatment of herpes encephalitis, neonatal herpes simplex virus infections, and, possibly, multiple sclerosis (7,28). Acute, reversible neuropsychiatric symptoms were first associated with acyclovir therapy in the early 1980s (26), and similar adverse effects have been reported for the use of valacyclovir (1,2,10,12,15,21,24).…”
mentioning
confidence: 95%
“…24 Raltegravir had no effect on inflammatory biomarkers and presence of CD 163, a marker of monocytes and macrophages. Three phase II clinical trials of acyclovir or its prodrug valacyclovir have been conducted in patients with MS. [8][9][10] Although they did not meet primary end points, there was a strong trend in the data, with a 34% reduction in ARR in acyclovir-treated patients, and subgroup analysis showed a significant reduction in relapse rate in favour of acyclovir treatment. 10 Moreover, in a predefined subgroup analysis, valacyclovir-treated patients with high disease activity at baseline had significant reduction in new lesions compared to a comparable group of placebo-treated patients.…”
Section: Antiviral Treatment Of Human Endogenous Retrovirus Infectimentioning
confidence: 99%
“…[8][9][10] All were conducted 20-30 years ago, before the era when disease-modifying immunomodulatory therapies were established in RRMS. No magnetic resonance imaging (MRI) was included in this study.…”
Section: Antiherpes Virus Treatment Of Msmentioning
confidence: 99%